Comparing the effect of usual bowel preparation and sodium phosphates preparation ‎method on patient acceptance under colonoscopy ‎ - maryam ebrahimmousavi; atefeh ghanbari; mahmuod yuosefi; tahereh khaleghduost; zahra atrkarruoshan (Guilan University of Medical Sciences, 2009)
Introduction: Colonoscopy is a method of endoscopy of lower gastrointestinal system which needs ‎proper colon preparation that allows proper assessment, diagnosis and treatment. There are different ‎methods of bowel preparation available. Therefore more research by critical nurses can result in ‎better care.‎ Objective: The aim of present study is to compare the routine method (Castor oil and Bisacodyl ‎tablet) and oral sodium phosphate on the level of patient s acceptance in patient undergoing ‎colonoscopy.‎ Methods: This is a Quasi-experimental study, which was done on ‎‏90‏‎ out patient candidates for ‎colonoscopy referring to Razi-educational center. Samples were randomly chosen on the visit day ‎and divided to ‎‏2‏‎ groups of experiment and control. Data collection instrument included a ‎demographic questionnaire and a checklist to assess the level of patient s acceptance and bowel ‎preparation. Primarily demographic data form was filled at that time, and then intervention was ‎done for two groups with ‎‏45‏‎ samples. The patient acceptance checklist was filled by interview ‎method on the day of performing colonoscopy procedure.‎ Results: Finding indicated that patient s acceptance was better with oral sodium phosphate and chi-‎square and Fisher s exact tests showed a significant difference on the level of patient s acceptance ‎‎(p< ‎‏0.000‏‎). ‎ Conclusion: According to this result oral liquid sodium phosphate has caused better acceptance ‎compared with routine regimes (Castor oil and Bisacodyl tablet) in patients under colonoscopy.‎